2014
DOI: 10.1074/jbc.m113.540088
|View full text |Cite
|
Sign up to set email alerts
|

Cholera Toxin Production during Anaerobic Trimethylamine N-Oxide Respiration Is Mediated by Stringent Response in Vibrio cholerae

Abstract: Background: Cholera toxin (CT) production is induced during anaerobic respiration with trimethylamine N-oxide (TMAO) in Vibrio cholerae. Results: A bacterial stringent response to nutrient starvation was activated during anaerobic TMAO respiration and influenced CT production. Conclusion: CT production during anaerobic TMAO respiration is mediated by stringent response in V. cholerae. Significance: A mechanism of TMAO-stimulated CT production is uncovered.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(34 citation statements)
references
References 63 publications
2
31
0
Order By: Relevance
“…Indeed, studies have shown that the virulence of enteric pathogens is associated with their ability to alter metabolic substrates in accordance with the intestinal environment of the host, which is constantly changing (45,46). Consistent with this notion, cholera toxin production was greatly induced when V. cholerae was grown by anaerobic TMAO respiration, a potential mode of growth that may occur inside the host intestine (31).…”
Section: Discussionsupporting
confidence: 65%
See 2 more Smart Citations
“…Indeed, studies have shown that the virulence of enteric pathogens is associated with their ability to alter metabolic substrates in accordance with the intestinal environment of the host, which is constantly changing (45,46). Consistent with this notion, cholera toxin production was greatly induced when V. cholerae was grown by anaerobic TMAO respiration, a potential mode of growth that may occur inside the host intestine (31).…”
Section: Discussionsupporting
confidence: 65%
“…Additionally, bacterial SR has been shown to be important to the persistent survival (62,63) and virulence (64,65) of bacterial pathogens. Likewise, a V. cholerae (p)ppGpp 0 mutant showed defective intestinal colonization and cholera toxin production, compared with its parental strain (31). The production of virulence factors has been shown to increase when bacterial cells encounter extracellular stress, often resulting in retarded growth (7, 66 -68).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The reduced needs of these cells appear to contribute significantly to environmental survival when conditions are unfavorable. Both QS and passage through a mammalian host return these cells to their active state, indicating that recovery from this state plays a significant role in transmission and the start of outbreaks (147150). …”
Section: Mechanisms Of Environmental Survival and Factors Influencingmentioning
confidence: 99%
“…Further, this increased production was suppressed when V. cholerae was unable to produce (p)ppGpp (Oh et al, 2014). In addition, CT production during the AKI condition (a biphasic growth to promote CT production; Iwanaga et al, 1986) is dependent on the cell's capability to produce (p)ppGpp (Oh et al, 2014).…”
Section: Resultsmentioning
confidence: 99%